Analysis of The Right to Live for Children of Adultery According to MUI Fatwa Number 11 of 2012 and Its Relation to MK Decision Number 46/PUU-VIII/2010 - Waris, A. Putri Dyana; Abbas, Abbas; Muntazar, Ahmad (Family Law Study Program (Ahwal Syakhshiyah), Universitas Muhammadiyah Makassar, 2024)
A child resulting from adultery cannot be assigned to the man who gave birth to him (his father), he can only be assigned to his mother and his mother's family. However, this does not eliminate the father's responsibility to provide for the child's living needs and provide assets after he dies through a mandatory will. MUI fatwa number 11 of 2012 rejected MK decision number 46/PUU-VIII/2010 which had previously been decided regarding children resulting from adultery who have civil rights with their father, if it is biologically proven that the child is a child resulting from adultery between their father and mother. The MUI fatwa stated that the MK decision deviated from Islamic teachings, according to which children resulting from adultery can only be assigned to their mother's family. To decide on a decision related to Islamic law, its formation must be in accordance with the basics of Islamic law and not deviate from it. In an effort to find the right decision for this problem, the author uses literature research by analyzing the MUI Fatwa and also the Constitutional Court's decision which explains the status of children, as well as sources that can provide information related to this research